2018
DOI: 10.1016/j.hpb.2017.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Pathological diaphragmatic invasion by colorectal liver metastases is associated with RAS mutation, peritoneal recurrence and worse survival

Abstract: Multiple tumors and RAS mutant were predictors for pathological diaphragmatic invasion, which was associated with a higher incidence of peritoneal recurrence and worse OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A positive margin (HR 3.36) and RAS mutation (HR 1.629) were independently associated with worse OS (40). Similarly, presence of RAS mutation is associated for more diaphragmatic invasion by liver metastasis requiring major hepatic resection and diaphragmatic resection (41). Margonis et al suggested that anatomical resections with more extensive surgical margins could counterbalance this adverse and more invasive genetic profile associated to RAS mutation (42).…”
Section: Impact Of Ras Mutation In Liver Metastases (Lim)mentioning
confidence: 99%
See 1 more Smart Citation
“…A positive margin (HR 3.36) and RAS mutation (HR 1.629) were independently associated with worse OS (40). Similarly, presence of RAS mutation is associated for more diaphragmatic invasion by liver metastasis requiring major hepatic resection and diaphragmatic resection (41). Margonis et al suggested that anatomical resections with more extensive surgical margins could counterbalance this adverse and more invasive genetic profile associated to RAS mutation (42).…”
Section: Impact Of Ras Mutation In Liver Metastases (Lim)mentioning
confidence: 99%
“…However, the role of tumor biology and RAS mutations in the context of PM remained unclear until recent studies (53)(54)(55)(56)(57). RAS mutation is associated with peritoneal recurrence after resection of LiM (41) and prevalence of RAS mutations appears higher in PM than in LiM, up to 58% (55). In 524 patients who underwent CRS and HIPEC for CRC PM, 378 had known RAS/ RAF status.…”
Section: Impact Of Ras Mutation In Peritoneal Metastases (Pm)mentioning
confidence: 99%